Adaptation of organizational commitment questionnaire in Indonesia - Rahmania, Fadhila; Islaha, Shafia (The International Journal of Politics and Sociology Research, 2023)
An employee's commitment to the company is one of the guarantees for maintaining the continuity of the organization, namely creating a sense of belonging to the company. Therefore, it is important to measure the role performance of employees in Indonesia. The organizational commitment measurement tool was first developed in 1982 by Steers, Porter and Mowday. This study aims to evaluate the validity and reliability of the Organizational Commitment Questionnaire (OCQ) measuring instrument in Indonesian. The analytical techniques used are Classical Test Theory (CTT) and Confirmatory Factor Analysis (CFA). Participants in this study were 227 employees (n = 370) who were taken using incidental sampling techniques. The adapted scale shows that it is reliable with Cronbach's Alpha of 0.853. In the results of Confirmatory Factor Analysis (CFA), the fit model is acceptable (RMSEA = 0.064 CFI = 0.952) which indicates that the data is in accordance with the research hypothesis, namely there is no difference between the matrix and the S matrix.